DETERMINATION OF CONSTANT FACTOR AND INDEX LEAF FOR RAPID LEAF AREA ESTIMATION IN TARO - Pardales Jr., JR (Annals of Tropical Research, 1980)
Five taro cultivars were selected from the germplasm at the Philippine Root Crop Research and Training Center in ViSCA, Baybay, Leyte to determine their estimated and actual leaf areas. Correlation analysis of the estimated and actual leaf areas revealed a high linear association between them. A general regression equation (Y-11.85 + 0.954X) was developed and further verified to be accurate in deter-mining the actual leaf area of taro by simply substituting the estimated leaf area (product of length x width) to the X in the equation. The same question can accurately determine the actual leaf area of different taro cultivars regardless of their stage of growth. The second leaf from the youngest open leaf was identified as the index leaf for both 3- and 4-leaf stage taro plants. The estimated area of the second leaf was highly correlated with the total plant leaf area. The regression equations Y = 9.12 + 2.785X and Y = 12.22 + 3.531X can be used to determine accurately the total leaf areas in 3- and 4-leaf stage taro plants, respectively.